Sugarcane grown in fertilized soil with sewage sludge: nutrients, heavy metals and productivity - Silva, Fábio Cesar da; Boaretto, Antônio Enedi; Berton, Ronaldo Severiano; Zotelli, Helder Basaglia; Pexe, Carlos Alberto; Mendonça, Elaine (Pesquisa Agropecuaria Brasileira, 1998)
The present research aimed to evaluate the effect of sewage sludge (SS) on nutrient and heavy metal absorption and productivity of sugarcane’s (Saccharum spp., var. RB72-454) ratoon. Sewage sludge was placed at 40 cm from plant row and at 15 cm depth, at the rates of 0, 15 and 30 t.ha-1. Sewage sludge decreased soil potential acidity (H + Al) and behaved as a source of Ca, P, S, Cu and Zn for sugarcane growth, as observed by the linear increases in biomass and sugar productivities. Addition of SS increased Ca, Cu, K, Mg, Ni, P and S exportations by sugarcane plant tops, as a result of their increases in plant tissue. Heavy metals (Cd, Cr, Ni e Pb) contents in the SS presented no danger to the trophic chain in short-time.